Uso de focus groups en investigación científica: Guía práctica para investigadores - Sanz-Marcos, Paloma (Infonomy, 2025)
This article offers a practical guide for researchers new to the qualitative technique of focus groups. Exploring their application, advantages and limitations, it provides a series of detailed recommendations for its correct implementation. Its objective is to serve as a useful tool for those seeking to understand and apply this technique.